The developing tool for heat exchanger education in instrumentation engineering - Oranpaiboon, Nurawit; Krongratana, Viriya; Tipsuwanpom, Vittaya; Gulpanich, Suphan (My University, 2016)
The purpose of this paper is to find out the method for constructing heat exchanger model that is a mathematical model comparing with balance energy technique. Firstly, the energy balance applies energy laws for calculating energy between hot and cold side of temperature which is the energy of input equal to energy of output and the result of this process is the outcome temperature would increase further to energy power that heater provides from hot side of heat exchanger. Secondly, Mathematical Model is related to using equations of thermal and finding transferred functions of system and variables of heat exchanger and simulation for responding viewing of output temperature. Finally, this project about energy balance and Mathematical Model would help some other plants in building plant model and calculating energy of system. The result of this method would help to compare between energy balance method and Mathematical Model and results outcome of both.
Keywords: Energy Balance; Heat exchanger; Mathematical Model; Project Based Learning